Pengaruh Promosi dan Service Quality Terhadap Kepuasan Pelanggan Pengguna Layanan Grab-Food pada Aplikasi Grab di Singaraja - Suratni, Ni Luh Saras; Mayasari, Ni Made Dwi Ariani (Universitas Pendidikan Ganesha, 2021)
This study was aimed to examine the effect of simultaneous and partially promotion and service quality on customer satisfaction of Grab-food service users on the Grab application in Singaraja. The number of samples in this study were 100 respondents, the sample technique used purposive sampling. The data method used a questionnaire. The data analysis technique in this research is quantitative using multiple linear regression analysis. The result of the study showed that (1) promotion and service quality has a positive and significant effect simultaneous on customer loyalty with a contribution influence of 62.1% and other variables was 37.9%. (2) promotion has a positive and significant effect partially on customer satisfaction with a contribution influence of 33.6%. (3) service quality has a positive and significant effect partially on customer satisfaction with a contribution influence of 11.2%.